2002
DOI: 10.1105/tpc.010274
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Rice Transcript Map Containing 6591 Expressed Sequence Tag Sites

Abstract: To determine the chromosomal positions of expressed rice genes, we have performed an expressed sequence tag (EST) mapping project by polymerase chain reaction-based yeast artificial chromosome (YAC) screening. Specific primers designed from 6713 unique EST sequences derived from 19 cDNA libraries were screened on 4387 YAC clones and used for map construction in combination with genetic analysis. Here, we describe the establishment of a comprehensive YAC-based rice transcript map that contains 6591 EST sites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 250 publications
(159 citation statements)
references
References 17 publications
3
153
0
3
Order By: Relevance
“…Previous studies have demonstrated signi®cant differences in recombination frequency along the length of each rice chromosome (Chen et al, 2002;Wu et al, 2002; Zhao et al, 2002). As these differences were detected by using whole YAC or BAC contigs rather than the interval region between each neighboring marker, this information on recombination frequency is of limited value for studies on gene isolation by map-based cloning.…”
Section: Recombination Frequency On Each Chromosomementioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies have demonstrated signi®cant differences in recombination frequency along the length of each rice chromosome (Chen et al, 2002;Wu et al, 2002; Zhao et al, 2002). As these differences were detected by using whole YAC or BAC contigs rather than the interval region between each neighboring marker, this information on recombination frequency is of limited value for studies on gene isolation by map-based cloning.…”
Section: Recombination Frequency On Each Chromosomementioning
confidence: 98%
“…During construction of the rice yeast arti®cial chromosome (YAC) physical map, the positions of the centromeres for 11 rice chromosomes were characterized by using the ricecentromere-speci®c sequence RCS2 as a probe (Wu et al, 2002). Recently, an extensive study was performed by thē uorescence in situ hybridization (FISH) technique with the aim of understanding the location, quantity, and organization of sequences of the CentO satellite (previously named RCS2) and Centromeric Retrotransposon of Rice (CRR ) within the rice centromere region .…”
Section: Integration Of Physical and Cytogenetic Mapsmentioning
confidence: 99%
See 3 more Smart Citations